Molecular mechanisms of obesity predisposes to atopic dermatitis - Shang, Dajin; Zhao, Shengnan (Frontiers in Immunology, 2024)
Obesity is a prevalent metabolic disease that reduces bacterial diversity, colonizes the epidermis with lipophilic bacteria, and increases intestinal pro-inflammatory species, all of which lead to impaired epithelial barriers. Adipose tissue secretes immunomodulatory molecules, such as adipokines, leptin, and adiponectin, which alters the morphology of adipocytes and macrophages as well as modulates T cell differentiation and peripheral Th2-dominated immune responses.Atopic dermatitis (AD) and obesity have similar pathological manifestations, including inflammation as well as insulin and leptin resistance. This review examines the major mechanisms between obesity and AD, which focus on the effect on skin and gut microbiota, immune responses mediated by the toll like receptor (TLR) signaling pathway, and changes in cytokine levels (TNF-a, IL-6, IL-4, and IL13). Moreover, we describe the potential effects of adipokines on AD and finally mechanisms by which PPAR-γ suppresses and regulates type 2 immunity.